2018
DOI: 10.1007/s00167-018-5171-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal tibial alignment is a risk factor for lateral meniscus posterior root tears in patients with anterior cruciate ligament ruptures

Abstract: Purpose The purpose of this study was to identify if abnormal tibial alignment was a risk factor for lateral meniscus posterior root tears (LMPRT) in patients with acute anterior cruciate ligament (ACL) ruptures. Methods The medical charts of 200 patients treated for ACL ruptures between 2013 and 2016 were retrospectively reviewed and evaluated. MRI images and reports were assessed for concurrent meniscal tears. Radiographs were reviewed for tibia vara and tibial slope angles and MRI reports identifying latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 26 publications
0
30
1
1
Order By: Relevance
“…The question remains as to whether or not the meniscus is protective after one of those injuries or more likely that the meniscus is at risk when there is a ligamentous injury that is not treated. Malalignment problems such as increased rotation of the femur or tibia 19,20 or increase varus or valgus of the knee may contribute to problems with meniscus tears-either leading to tears, nonhealing of repairs, or contributing to arthritis after meniscal tears. 21,22 The Discoid Meniscus…”
Section: Associated Problemsmentioning
confidence: 99%
“…The question remains as to whether or not the meniscus is protective after one of those injuries or more likely that the meniscus is at risk when there is a ligamentous injury that is not treated. Malalignment problems such as increased rotation of the femur or tibia 19,20 or increase varus or valgus of the knee may contribute to problems with meniscus tears-either leading to tears, nonhealing of repairs, or contributing to arthritis after meniscal tears. 21,22 The Discoid Meniscus…”
Section: Associated Problemsmentioning
confidence: 99%
“…8,12,19,40,48 Moreover, it was recently reported that knee alignment might affect medial meniscal extrusion, which could increase the risk of developing osteoarthritis, 11,34 the tibiofemoral contact force, 46 and even the incidence of root tears in the lateral and medial menisci. 6,18,35 However, a paucity of literature on this subject makes it difficult to find an association between knee alignment and ramp lesions.…”
mentioning
confidence: 99%
“…1,15 Specifically, lateral meniscus posterior root tears have a reported incidence ranging from 7% to 15% at the time of ACL reconstruction (ACLR). 11,17,19 However, there are limited outcome data regarding the success rates of first-stage meniscal repair healing in patients who undergo 2-stage revision ACLR. 2,3…”
mentioning
confidence: 99%